Defect tolerant and dimension dependent ferromagnetism in MnSe2. Issue 30 (19th July 2019) - Eren, I.; Iyikanat, F.; Sahin, H.
Abstract : By performing density functional theory-based calculations, we investigate the structural, vibrational, electronic and magnetic properties of 2D monolayers, nanoribbons and quantum dots of MnSe2 . Abstract : By performing density functional theory-based calculations, we investigate the structural, vibrational, electronic and magnetic properties of 2D monolayers, nanoribbons and quantum dots of MnSe2 . Vibrational spectrum analysis reveals the dynamical stability of not only ferromagnetic but also antiferromagnetic phases of single layer MnSe2 crystal structures. Electronically, calculations show that 1T-MnSe2 is a ferromagnetic structure displaying metallic behavior. It is also found that the structure preserves its dynamical stability and metallic behavior even under the presence of high density Se vacancies. Moreover, it was predicted that, differing from the 2D MnSe2, metal–metal interaction driven reconstructions result in ferromagnetic-to-antiferromagnetic crossover in the ground state of nanoribbons and quantum dots. With its robust ferromagnetic metallic character in the 2D ultra-thin limit and dimension-dependent magnetic properties, MnSe2 is an important candidate for spintronic device applications.